Association between adjuvant regional radiotherapy and cognitive function in breast cancer patients treated with conservation therapy. (23rd April 2014) - Shibayama, Osamu; Yoshiuchi, Kazuhiro; Inagaki, Masatoshi; Matsuoka, Yutaka; Yoshikawa, Eisho; Sugawara, Yuriko; Akechi, Tatsuo; Wada, Noriaki; Imoto, Shigeru; Murakami, Koji; Ogawa, Asao; Akabayashi, Akira; et al.
Abstract Although protracted cognitive impairment has been reported to occur after radiotherapy even when such therapy is not directed to brain areas, the mechanism remains unclear. This study investigated whether breast cancer patients exposed to local radiotherapy showed lower cognitive function mediated by higher plasma interleukin (IL)‐6 levels than those unexposed. We performed the Wechsler Memory Scale‐Revised (WMS‐R) and measured plasma IL‐6 levels for 105 breast cancer surgical patients within 1 year after the initial therapy. The group differences in each of the indices of WMS‐R were investigated between cancer patients exposed to adjuvant regional radiotherapy (n = 51) and those unexposed (n = 54) using analysis of covariance. We further investigated a mediation effect by plasma IL‐6 levels on the relationship between radiotherapy and the indices of WMS‐R using the bootstrapping method. The radiotherapy group showed significantly lower Immediate Verbal Memory Index and Delayed Recall Index (P = 0.001, P = 0.008, respectively). Radiotherapy exerted an indirect effect on the lower Delayed Recall Index of WMS‐R through elevation of plasma IL‐6 levels (bootstrap 95% confidence interval = −2.6626 to −0.0402). This study showed that breast cancer patients exposed to adjuvant regional radiotherapy in conservation therapy might have cognitive impairment even several months after their treatment. The relationship between the therapy and the cognitive impairment could be partially mediated by elevation of plasma IL‐6 levels.